Hematologic adaptation to mask‐wearing among pregnant women and obstetrical outcome during the coronavirus disease 2019 pandemic. Issue 2 (12th May 2021) - Friedrich, Lior; Levin, Gabriel; Maixner, Nitzan; Bart, Yossi; Tsur, Abraham; Yinon, Yoav; Meyer, Raanan
Abstract: Objective: To evaluate the effect of the coronavirus disease 2019 (COVID‐19) mask‐wearing on hematological laboratory components and obstetrical outcomes among women delivering during the COVID‐19 pandemic. Methods: Laboratory results and obstetrical outcomes of women with singleton gestations, admitted for delivery during the COVID‐19 mask‐wearing period (April–June 2020) were compared with those of women delivering during the parallel period in 2019 and with a larger cohort derived from nine pre‐pandemic years (March 2011–April 2020). Results: Overall, 1838 women delivered during the COVID‐19 pandemic. Compared with the pre‐pandemic period, mean hemoglobin and fibrinogen levels were significantly higher during the mask‐wearing period (12.15 ± 1.1 vs 11.96 ± 1.2, P < 0.001 and 472 ± 103.6 vs 448 ± 85.1 mg/dl, P < 0.001, respectively). Platelet levels were lower (200 ± 56.0 vs 206 ± 57.5 K/µl, P < 0.001). The rate of delivery at <34 weeks of gestation was lower during the mask‐wearing period (1.1% vs 2%, odds ratio [OR] 0.57, 95% confidence intervals [CI] 0.37–0.88, P = 0.01), whereas cesarean delivery and postpartum hemorrhage rates were higher (26.7% vs 24.4%, OR 1.13, 95% CI 1.02–1.25, P = 0.022 and 4.1% vs 2.8%, OR 1.5, 95% CI 1.2–1.8, P = 0.001, respectively). Conclusion: A hard‐to‐ventilate space created by wearing a mask during the COVID‐19 era may be the underlying cause of the observed higher hemoglobin level among pregnant women, possibly affecting obstetrical outcomes. Synopsis: Hematologic adaptations, possibly facilitated by a hard‐to‐ventilate space created by wearing a mask during the COVID‐19 era, may affect obstetrical outcome.